Resilience, quality of life and symptoms of depression among elderlies receiving outpatient care - Gabriella Santos Lima; Isabela Maria Oliveira Souza; Luana Baldin Storti; Mônica Maria de Jesus Silva; Luciana Kusumota; Sueli Marques (Universidade de São Paulo, 2019)
Objective: to analyze the relation between resilience and demographic variables, quality of life and symptoms of depression in elderlies attended at a Geriatric Outpatient Clinic. Method: analytical cross-sectional study, conducted with 148 elderlies, with a questionnaire of sociodemographic and health characterization, the Resilience Scale, the World Health Organization Quality of Life Bref, the World Health Organization Quality of Life Old, and the Center for Epidemiologic Survey - Depression Scale. Descriptive statistics, Student's t-test and Pearson correlation were used for data analysis. Results: there was a positive correlation between resilience and schooling (r = 0.208; p = 0.010), income (r = 0.194; p = 0.017), the World Health Organization Quality of Life Bref (r = 0.242; p = 0.003), and the World Health Organization Quality of Life Old (r = 0.522; p <0.001), and negative correlation regarding symptoms of depression (r = -0.270; p = 0.001). Conclusion: Resilience presented relation to schooling, income, quality of life and symptoms of depression in the elderly. These results are expected to help the multidisciplinary team plan actions aimed at developing resilience towards the promotion of health and good quality of life in old age.